Life of Cops at Work Areas and their Social Relationships with the Society - Chakravarthy, Parle Kalyan (International Journal of Bio-resource and Stress Management, 2020)
Stress is a symptom of imbalance in health in daily life. The more stress, the individual health life becomes more painful. It is a psychological disorder for every individual who is in pressure, anxiety, hyper tension and so on. From the Two-corner side of stress, sometimes the Eu-stress brings positive nature in individual life and sometimes the distress makes people conscious. Stressors always suffer with psychological, Physical health problems when they are in duty which also reflects in the work-life balance with family members. Sometimes they face burnout situations which lead to suicidal thoughts and also burnout occurs more frequently among professionals who work with other persons, especially as service providers while they face with them by some situations. This paper focussed on the two district Police Constables to find the stress levels at work. The districts are in Odisha state i.e. Gajapathi district, border to Andhra Pradesh and Nuapada District, border to Chhattisgarh state to find the outcomes associated with Social and individual life. Data has been analysed by Independent T-test, Pearson Correlation test and also Factor analysis has been taken to find the gender wise with social domain variables and descriptive statistics has been taken to find the general values. Findings and suggestions has been given based on the results and along with the strategies to make them free with situational stress life.